Querying top-down, bottom-up implementation guidelines : education policy implementation in Jamaica - Chunnu-Brayda, Winsome (2012)
Explores top-down and bottom-up implementation approaches, as well as model theory. Concludes by highlighting five major findings and suggestions for policy implementation.